Study of management of Indonesian Coastal and Marine seas (Review: Benoa Bay Reclamation) - Putra, Rahmat Wahyudi; Firmansyah, Raja Muhammad; Wagianto, Wagianto; Gunansyah, Gunansyah; Kamal, Eni (Universitas Malikussaleh, 2021)
Benoa Bay is part of the waters of Bali which contributes very positively to the Balinese people, especially to the surrounding community, especially in maintaining the stability of various ecosystems and hydrology as well as its contribution in providing protection, economic, and socio-cultural services for the local community. Proper management of the Benoa Bay area will be able to minimize the risks that will occur. Therefore, good management of coastal and marine areas is needed through an integrated management program that is supported by the availability of objective, accurate, and up-to-date information sources. This study was carried out by collecting literature from relevant research on reclamation in Benoa Bay. The results of the study found that PT. Tirta Wahana Bali International (PT. TWBI) as the holder of the Benoa Bay Utilization and Development permit will develop the Benoa Bay area including (1) Pudut Island Restoration; (2) Firsherman's Cove; (3) Botanical Garden, meanwhile the Benoa Bay area is a center of biodiversity and there is a high and complete diversity of ecosystems, namely; Ecosystems of mangroves,coral reefs,seagrass beds, andtidal flats. This illustrates that integrated management must and immediately be carried out to assist in the formulation of policies and planning for the management of coastal and marine areas that are more effective and targeted so that there are no mistakes in policy making that lead to social conflicts.Keywords: Benoa Bay, ecosystem diversity, integrated program, policy